Corporate governance in newly listed companies - David B. Audretsch; Erik E. Lehmann (University of Augsburg, Chair of Management and Organization, 2013)
Topics in corporate governance have been around in the literature almost for a century, most of the theoretical and empirical work has focused on the large and public company. While this research has improved our understanding of how large corporations are governed, corporate governance in small and medium sized enterprises and in particular in entrepreneurial and newly listed firms has rarely been studied. This essay offers a reflective overview of corporate governance mechanisms in entrepreneurial and newly listed companies and of why and how governance mechanisms differ from those in large and publicly traded corporations. In contrast to the traditional approach in corporate governance, we do not rely on the agency perspective as a work-horse to analyze governance problems. Instead we focus on either market or institutional based mechanisms in corporate governance. This opens the view on governance problems in newly listed companies outside the narrow view of either an agency or free-market perspective. Instead, the following study tries to bridge the different perspectives on corporate governance. From the broad set of mechanisms in corporate governance discussed in the literature, we focus only on a small subset which is prevalent in newly listed companies like the product and capital market, the market for corporate control, boards of directors and capital structures.
Keywords: 650